Localization of the E6-AP regions that direct human papillomavirus E6 binding, association with p53, and ubiquitination of associated proteins. - Huibregtse, J M (1993)
E6-AP is a 100-kDa cellular protein that mediates the interaction of the human papillomavirus type 16 and 18 E6 proteins with p53. The association of p53 with E6 and E6-AP promotes the specific ubiquitination and subsequent proteolytic degradation of p53 in vitro. We recently isolated a cDNA encoding E6-AP and have now mapped functional domains of E6-AP involved in binding E6, association with p53, and ubiquitination of p53. The E6 binding domain consists of an 18-amino-acid region within the central portion of the molecule. Deletion of these 18 amino acids from E6-AP results in loss of both E6 and p53 binding activities. The region that directs p53 binding spans the E6 binding domain and consists of approximately 500 amino acids. E6-AP sequences in addition to those required for formation of a stable ternary complex with E6 and p53 are necessary to stimulate the ubiquitination of p53. These sequences lie within the C-terminal 84 amino acids of E6-AP. The entire region required for E6-dependent ubiquitination of p53 is also required for the ubiquitination of an artificial E6 fusion protein.